RELIGIOUS INTERFACE OF SUSTAINABLE DEVELOPMENT FOR PEOPLE - Nandhikkara, Jose (Journal of Dharma, 2022)
In the Preamble of the SDG Agenda, we read: “We are determined to end poverty and hunger, in all their forms and dimensions, and to ensure that all human beings can fulfil their potential in dignity and equality and in a healthy environment.” People are the focus of the SDGs, especially the first five goals deal directly with the fundamental needs and well-being of people. Global poverty is a severe problem, interlinked with hunger, health, education, and gender equality. The poorest in the world are often hungry, sick, and illiterate, and the women and children suffer and are discriminated against more. Religions play significant roles in eradicating poverty by providing basic human needs – food, water, health, and education. Religious organisations provide more than half of the educational and a third of the medical facilities to people worldwide. Though often accused of human rights violations and discrimination against women, religions today contribute significantly towards promoting human rights and women empowerment.